Do the ‘Valentine’s Day Blues’ Exist? A Legacy Report on a Purported Psychological Phenomenon - Lange, Rense; Jerabek, Ilona; Dagnall, Neil (Journal of Scientific Exploration, 2022)
The ‘Valentine’s Day Blues’ is an enduring concept rooted in pop psychology that has unfortunately received little empirical attention. On this point, it is commonly assumed that the increasing commodification of romance plus the social trappings of Valentine’s Day can elicit stresses similar to those evoked by traditional holidays. Thus, women’s greater experience of ‘mattering’ and greater tendencies towards depression and rumination should place women at a greater risk of ‘Valentine’s Day Blues’ than men. Accordingly, when no Valentine’s Day gift is received such distress likely lasts longer in women than in men in addition to being stronger in general. These hypotheses were tested based on the data of 2,070 participants in a 2004 consumer sentiment survey who completed a 34-item online questionnaire within four weeks following Valentine’s Day. This questionnaire addressed anxiety, depression, rumination, and social anxiety as derived from existing instruments. Rasch scaling analyses found that men and women’s generalized depression (i.e., a combination of the four aforementioned item types) was greater for those not receiving a gift relative to that expressed by those who did receive a Valentine’s Day gift. However, while men rebounded after two weeks, women’s greater depression continued after three weeks. Of greatest clinical concern are 30-40 year olds, and those least affected were respondents over 40 years of age. Keywords: Emotion regulation, holiday depression, pop psychology, Rasch scaling, stress reactions